STRATEGI KOMUNIKASI PEMASARAN EVENT ELEMENTARY SCHOOL GAMES OLEH PT. DBL INDONESIA DALAM MEMBANGUN BRAND IMAGE EVENT BARU - Pratama, Satria Deva; M.I. Kom., Mutiah. S.sos. (The Commercium, 2023)
Descriptive research with a qualitative approach with the title: Marketing Communication Strategy Event Elementary School Games by PT. DBL Indonesia in Building a New Brand Image Event. This study aims to find out about the marketing communication strategy for the Elementary School Games (ESG) event by PT. DBL Indonesia in building a new brand image event. The research method used in this research is descriptive qualitative method. In the research on the Marketing Communication Strategy of the Elementary School Games Event by PT. DBL Indonesia in Building a New Brand Image Event obtained research results including: There were 35 elementary school participants who took part in the ESG event in the city of Surabaya. Of the 35 participants, the majority came from elementary schools in the city of Surabaya, while the others were in the cities of Sidoarjo, Malang and Mojokerto. The promotional agenda carried out by PT. DBL Indonesia, through its varied publication content, utilizing various official timelines is one of the most effective ways during the event. This is evidenced by the current number of followers on the ESG PT Instagram Official Account. DBL Indonesia, has 21,000 followers. Then implicitly through the twibbon content, the management of PT. DBL Indonesia personally invites each participant to publish Twibbon on their personal account. Keyword: ESG, Marketing Communication Stategy, PT. DBL Indonesia